Robust modeling for thermal error of spindle of slant bed lathe based on error decomposition - Shi, Hu; Qu, Qiangqiang; Mei, Xuesong; Tao, Tao; Wang, Haitao (Case studies in thermal engineering, 2023)
Thermal error of spindle is critical to the slant bed CNC lathe towards high machining precision. The heat generated by the spindle itself contributes to the thermal error indeed. However, the thermal error is also influenced by the thermal deformation of other components such as the turret and lathe bed, especially in complex structured slant-bed CNC lathes where error coupling commonly exists. In order to achieve robust modeling of thermal error, a decomposition method was proposed in this paper to separate the contributions of spindle, turret and lathe bed from the overall measured thermal deformation. The thermal error coupling relationship was established from the perspective of machine tool construction. A specific testing scheme was designed to determine the parameters of decoupling model. Additionally, a comparative experiment was carried out by placing the sensor support horizontally and vertically to verify the effectiveness of thermal error decoupling. Taking T65-750 high-precision CNC lathe as the object, the relationship between thermal error and tilt angle in the X-direction of the headstock, bed, and other components was revealed, achieving robust prediction of thermal error irrespective of the ambient temperature subject to change. Finally, the thermal error model built based on error decomposition was applied to improve the machining accuracy of cylindrical parts dramatically in practice.